Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's go through each multiplication step-by-step to determine the correct answers:
1. [tex]\(3 \times (-1) = -3\)[/tex]
- Multiplying a positive number by a negative number results in a negative number.
2. [tex]\((-12) \times (-11) \times 10 = 1320\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-12) \times (-11) = 132\)[/tex].
- Then, multiplying the positive result by a positive number retains the positivity: [tex]\(132 \times 10 = 1320\)[/tex].
3. [tex]\((-1) \times 225 = -225\)[/tex]
- Multiplying a negative number by a positive number results in a negative number.
4. [tex]\((-1) \times (-2) \times (-3) = -6\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-1) \times (-2) = 2\)[/tex].
- Then, multiplying a positive number by a negative number results in a negative number: [tex]\(2 \times (-3) = -6\)[/tex].
5. [tex]\((-15) \times 0 = 0\)[/tex]
- Multiplying any number by zero results in zero.
6. [tex]\((-21) \times (-30) = 630\)[/tex]
- Multiplying two negative numbers gives a positive number.
7. [tex]\((-18) \times (-5) \times (-4) = -360\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-18) \times (-5) = 90\)[/tex].
- Then, multiplying a positive number by a negative number results in a negative number: [tex]\(90 \times (-4) = -360\)[/tex].
8. [tex]\((-3) \times (-6) \times (-2) \times (-1) = 36\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-3) \times (-6) = 18\)[/tex].
- Multiplying the positive result by another negative number results in a negative number: [tex]\(18 \times (-2) = -36\)[/tex].
- Finally, multiplying a negative number by a negative number gives a positive number: [tex]\(-36 \times (-1) = 36\)[/tex].
9. [tex]\((-316) \times (-1) = 316\)[/tex]
- Multiplying two negative numbers gives a positive number.
Thus, the results are:
[tex]\[ \begin{array}{l} 3 \times (-1) = -3 \\ (-12) \times (-11) \times 10 = 1320 \\ (-1) \times 225 = -225 \\ (-1) \times (-2) \times (-3) = -6 \\ (-15) \times 0 = 0 \\ (-21) \times (-30) = 630 \\ (-18) \times (-5) \times (-4) = -360 \\ (-3) \times (-6) \times (-2) \times (-1) = 36 \\ (-316) \times (-1) = 316 \\ \end{array} \][/tex]
1. [tex]\(3 \times (-1) = -3\)[/tex]
- Multiplying a positive number by a negative number results in a negative number.
2. [tex]\((-12) \times (-11) \times 10 = 1320\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-12) \times (-11) = 132\)[/tex].
- Then, multiplying the positive result by a positive number retains the positivity: [tex]\(132 \times 10 = 1320\)[/tex].
3. [tex]\((-1) \times 225 = -225\)[/tex]
- Multiplying a negative number by a positive number results in a negative number.
4. [tex]\((-1) \times (-2) \times (-3) = -6\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-1) \times (-2) = 2\)[/tex].
- Then, multiplying a positive number by a negative number results in a negative number: [tex]\(2 \times (-3) = -6\)[/tex].
5. [tex]\((-15) \times 0 = 0\)[/tex]
- Multiplying any number by zero results in zero.
6. [tex]\((-21) \times (-30) = 630\)[/tex]
- Multiplying two negative numbers gives a positive number.
7. [tex]\((-18) \times (-5) \times (-4) = -360\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-18) \times (-5) = 90\)[/tex].
- Then, multiplying a positive number by a negative number results in a negative number: [tex]\(90 \times (-4) = -360\)[/tex].
8. [tex]\((-3) \times (-6) \times (-2) \times (-1) = 36\)[/tex]
- Multiplying two negative numbers gives a positive number: [tex]\((-3) \times (-6) = 18\)[/tex].
- Multiplying the positive result by another negative number results in a negative number: [tex]\(18 \times (-2) = -36\)[/tex].
- Finally, multiplying a negative number by a negative number gives a positive number: [tex]\(-36 \times (-1) = 36\)[/tex].
9. [tex]\((-316) \times (-1) = 316\)[/tex]
- Multiplying two negative numbers gives a positive number.
Thus, the results are:
[tex]\[ \begin{array}{l} 3 \times (-1) = -3 \\ (-12) \times (-11) \times 10 = 1320 \\ (-1) \times 225 = -225 \\ (-1) \times (-2) \times (-3) = -6 \\ (-15) \times 0 = 0 \\ (-21) \times (-30) = 630 \\ (-18) \times (-5) \times (-4) = -360 \\ (-3) \times (-6) \times (-2) \times (-1) = 36 \\ (-316) \times (-1) = 316 \\ \end{array} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.